Meta-Analysis of the Expansion in the Field of Structural Biology of ABC Transporters - Soomi Kim; Teena Bajaj; Cole Chabon; Eric Tablante; Tatyana Kulchinskaya; Tae Seok Moon; Ruchika Bajaj (BioDesign Research, 2022)
ABC transporters are molecular machines which power the solute transport using ATP hydrolysis. The structural biology of ABC transporters has been exploding for the last few years, and this study explores timelines and trends for various attributes such as structural tools, resolution, fold, sources, and group leaders. This study also evidences the significance of mammalian expression systems, advancements in structural biology tools, and the developing interest of group leaders across the world in the remarkably progressing field. The field started in 2002 and bloomed in 2016, and COVID years were really productive to the field. Specifically, the study explores 337 structures of 58 unique ABC transporters deposited in the PDB database from which P-glycoprotein has the largest number of structures. Approximately, 62% of total structures are determined at the resolution of 3-4 Å and 53% of structures belong to fold IV type. With progressive advancements in the field, the field is shifting from prokaryotic to eukaryotic sources and X-ray crystallography to cryoelectron microscopy. In the nutshell, this study uniquely provides the detailed snapshot of the field of structural biology of ABC transporters with real-time data.